Updates on the Use of Neoadjuvant Therapy in Borderline Resectable Pancreatic Cancer - Chandhok, Namrata Sonia; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Pancreatic cancer is an aggressive and devastating cancer that continues to have high 5-year mortality rates despite advancements in the field. Surgery remains the only curative treatment; however, most patients present with late stage disease deemed unresectable. By refining the resection guidelines to include a borderline resectable group, as well as advancements in neoadjuvant chemotherapy and radiation that improve resectability, we may improve upon outcomes for patients with more invasive disease. Here we summarize and discuss findings presented at the 2014 ASCO Gastrointestinal Cancers Symposium (Abstracts #283, #302, #309, #274, #275, #327) that relate neoadjuvant therapeutic strategies and borderline resectable cancers. Image: Tufts Medical Center. Boston, MA, USA